A Distinct Tetradentate N2O2‐type Ligand: (o‐Carboranyl)bis(2‐hydroxymethyl)pyridine1. Issue 7 (9th April 2013) - Di Salvo, Florencia; Teixidor, Francesc; Viñas, Clara; Giner Planas, José
Abstract A new chiral racemic ligand (o‐carboranyl)bis(2‐hydroxymethyl)pyridine oCB(hmpH)2, that is composed of a central o‐carborane unit where two arms radiate out of the cluster carbons each one containing a 2‐pyridylmethylalcohol chelating arms, provides two potentially bidentate NO or one tetradentate N2O2 binding pockets. An unprecedented octahedral CoII complex [CoCl2(anti‐oCB(hmpH)2] was obtained under aerobic conditions and characterized by X‐ray crystallography as well as IR and NMR spectroscopy. anti‐oCB(hmpH)2 acts as a tetradentate N2O2‐ligand affording the complex as a racemic mixture of cis‐α Δ‐[CoCl2(RRanti‐oCB(hmpH)2)] and Λ‐[CoCl2(SSanti‐oCB(hmpH)2)]. The new ligand oCB(hmpH)2 appears to be suitable for producing a variety of new chiral‐at‐metal complexes.